Drug-induced severe cutaneous adverse reactions in a patient after COVID-19 infection. Case report - Peñaloza Daguer, Denys E.; Di Prinzio, Anamá; Echeverría, María; Cura, María J.; Mazzuoccolo, Luis D.; Bustamante, Lucrecia; Torre, Ana C. (Revista del Hospital Italiano de Buenos Aires, 2023)
During the COVID-19 pandemic, various adverse drug reactions were observed. This could have been related to a greater immunological susceptibility of patients with SARS-CoV-2 to present this type of symptoms, as well as exposure to multiple drugs used in their treatment. We report the case of a patient with a severe respiratory infection due to COVID-19, who presented 2 serious adverse drug reactions associated with paracetamol in a short period of time.
Keywords: SARS-CoV-2; COVID-19; toxic epidermal necrolysis; acute exanthematous pustulosis; adverse drug reaction